2021
DOI: 10.3390/v13061143
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Antigenemia as a Confounding Factor in Immunodiagnostic Assays: A Case Study

Abstract: Humoral immunity has emerged as a vital immune component against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Nevertheless, a subset of recovered Coronavirus Disease-2019 (COVID-19) paucisymptomatic/asymptomatic individuals do not generate an antibody response, constituting a paradox. We assumed that immunodiagnostic assays may operate under a competitive format within the context of antigenemia, potentially explaining this phenomenon. We present a case where persistent antigenemia/viremia was… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
(49 reference statements)
0
11
0
Order By: Relevance
“…In order to detect SARS-CoV-2 in lung tissue we developed monoclonal antibodies which react against receptor-binding domain (RBD) of the spike protein of SARS-CoV-2 and identified a high affinity antibody (G2), the validity of which was recently verified [ 38 ] ( Figure S1 , Table S1 ). SARS-CoV-2 was detected (using both our “in house” G2 clone and a commercially available antibody from GeneTek) predominantly in alveolar type 2 (AT2) cells, which were identified by TTF-1 and Surfactant Protein B (SP-B) positivity, and in sparse inflammatory cells (alveolar and tissue macrophages) in all COVID-19 patients, ranging from <5 cells/4mm 2 tissue to >50 cells/4mm 2 tissue ( figure 1a , Table S1A ).…”
Section: Resultsmentioning
confidence: 99%
“…In order to detect SARS-CoV-2 in lung tissue we developed monoclonal antibodies which react against receptor-binding domain (RBD) of the spike protein of SARS-CoV-2 and identified a high affinity antibody (G2), the validity of which was recently verified [ 38 ] ( Figure S1 , Table S1 ). SARS-CoV-2 was detected (using both our “in house” G2 clone and a commercially available antibody from GeneTek) predominantly in alveolar type 2 (AT2) cells, which were identified by TTF-1 and Surfactant Protein B (SP-B) positivity, and in sparse inflammatory cells (alveolar and tissue macrophages) in all COVID-19 patients, ranging from <5 cells/4mm 2 tissue to >50 cells/4mm 2 tissue ( figure 1a , Table S1A ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to sputum, nasopharyngeal swab, nasal swab and saliva specimens, blood samples (serum and plasma) are promising for antigen testing, especially as collection of blood samples is associated with a much lower risk of contracting the infection during sampling. A few reports to date have demonstrated that the nucleocapsid antigen (N antigen) of SARS-CoV-2 can be detected in the plasma by enzyme-linked immunosorbent assay, chemiluminescence enzyme immunoassay, and a highly sensitive single molecule array immunoassay, although the clinical significance of the N antigen in blood samples of COVID-19 patients is not yet fully understood ( Ogata et al, 2020 ; Belogiannis et al, 2021 ; Deng et al, 2021 ; Le Hingrat et al, 2021 ; Perna et al, 2021 ; Shan et al, 2021 ). Considering that several previous studies have demonstrated that SARS-CoV-2 RNA titers in blood samples are associated with the severity of COVID-19 ( Eberhardt et al, 2020 ; Fajnzylber et al, 2020 ; Wölfel et al, 2020 ; Di Cristanziano et al, 2021 ), antigen testing in blood samples might be useful for predicting the severity of COVID-19 as well as for diagnosing the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Interpretation of the above data is not straightforward, due to marked differences across studies in terms of patient characteristics, particularly the analytical features of the immunoassays employed, type of specimen processed (sera or plasma), use of unique or sequential specimens, and timing of sample collection after symptoms onset. In addition, since immunoassays are only capable of detecting either antibodies in a free state or antigen–antibody immunocomplexes with available antibody binding sites 22 , elucidating the biological form of the virus present in blood (either infectious or defective genome viral particles, free viral components or both) may help to correctly interpret virus–antibody dynamics. In this respect, by using a RT-PCR viability assay we showed that within the timeframe examined, most viral RNA present in blood is likely in a non-capsidated state, indicating that the main source of viral products (RNA and proteins) in blood could be PANoptosis in the URT 22 ; nonetheless, one out of seven plasma specimens yielded a RT-PCR viability profile compatible with presence of capsidated (protected) virus RNA.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, since immunoassays are only capable of detecting either antibodies in a free state or antigen–antibody immunocomplexes with available antibody binding sites 22 , elucidating the biological form of the virus present in blood (either infectious or defective genome viral particles, free viral components or both) may help to correctly interpret virus–antibody dynamics. In this respect, by using a RT-PCR viability assay we showed that within the timeframe examined, most viral RNA present in blood is likely in a non-capsidated state, indicating that the main source of viral products (RNA and proteins) in blood could be PANoptosis in the URT 22 ; nonetheless, one out of seven plasma specimens yielded a RT-PCR viability profile compatible with presence of capsidated (protected) virus RNA. In this sense, apparently intact virus particles have been observed in plasma pellets using electron tomography and immunostaining 3 ; of note, that latter specimen was obtained early after symptoms onset (3 days), suggesting that the presence of intact virions in the bloodstream may be restricted to a narrow window close to the time of contracting the infection.…”
Section: Discussionmentioning
confidence: 99%